Impacts of water level regulation on trophic niche and growth of Arctic charr (Salvelinus alpinus) and brown trout (Salmo trutta) in Norwegian hydropower reservoirs - Kytökorpi, Mikko Antero (UiT Norges arktiske universitet, 2019)
Hydropower is among the largest renewable energy sources globally. However, it can have drastic environmental and socio-economic impacts on dammed lakes (i.e., reservoirs) and rivers where water levels are regulated due to hydropower operations. Water level regulation in hydropower reservoirs is known to be a large environmental problem, leading to changes in the abiotic conditions, which subsequently affect biological productivity and diversity and thereby may also change the trophic niche and life-history traits of top predators. Arctic charr and brown trout often coexist in subarctic lakes and hydropower reservoirs, and as top predators, they are suitable indicators for changes in the lake ecosystems. In the present study, the effects of water level regulation on trophic niche and life-history traits of Arctic charr and brown trout were studied in 14 subarctic lakes in northern Norway. Age, length, maturity, diet and stable isotope data were compared from seven regulated and seven unregulated lakes. Both charr and trout were expected to show different diet, lower littoral reliance, lower trophic position, slower growth and later maturation in regulated lakes compared to unregulated lakes. This study indicated less effect on fish predators than were expected based on previous studies of reservoir fish populations, but some expected results were also found. Charr did not show any differences in diet, trophic position or growth between the lake types. Moreover, they were found to rely more on littoral resources and to mature at a smaller size in regulated lakes than in unregulated lakes. As hypothesised, trout were found to have a different diet, lower trophic position, slower growth and higher age at maturation in regulated lakes than in unregulated lakes. However, trout also relied more on littoral resources in regulated lakes compared to unregulated lakes. The results were supported by previous studies indicating that charr with a more plastic niche can utilize alternative food and habitat resources, whereas ...